A bioorthogonal chemistry approach to detect the K1 polysialic acid capsule in Escherichia coli. Issue 2 (4th January 2023) - Rigolot, Vincent; Rossez, Yannick; Biot, Christophe; Lion, Cédric
Abstract : A metabolic oligosaccharide engineering method that enables bioorthogonal labelling of the K1 capsule expressed by pathogenic Escherichia coli strains associated with neonatal meningitis and sepsis. Abstract : Most Escherichia coli strains associated with neonatal meningitis express the K1 capsule, a sialic acid polysaccharide that is directly related to their pathogenicity. Metabolic oligosaccharide engineering (MOE) has mostly been developed in eukaryotes, but has also been successfully applied to the study of several oligosaccharides or polysaccharides constitutive of the bacterial cell wall. However, bacterial capsules are seldom targeted despite their important role as virulence factors, and the K1 polysialic acid (PSA) antigen that shields bacteria from the immune system still remains untackled. Herein, we report a fluorescence microplate assay that allows the fast and facile detection of K1 capsules with an approach that combines MOE and bioorthogonal chemistry. We exploit the incorporation of synthetic analogues of N -acetylmannosamine or N -acetylneuraminic acid, metabolic precursors of PSA, and copper-catalysed azide–alkyne cycloaddition (CuAAC) as the click chemistry reaction to specifically label the modified K1 antigen with a fluorophore. The method was optimized, validated by capsule purification and fluorescence microscopy, and applied to the detection of whole encapsulated bacteria in a miniaturized assay. We observe that analogues of ManNAc are readily incorporated into the capsule while those of Neu5Ac are less efficiently metabolized, which provides useful information regarding the capsule biosynthetic pathways and the promiscuity of the enzymes involved. Moreover, this microplate assay is transferable to screening approaches and may provide a platform to identify novel capsule-targeted antibiotics that would circumvent resistance issues.